The Constitution of Somalia on Paper and the Constitutional Reality - Kouroutakis, Antonios (SSRN, 2018)
Somalia in 2012 adopted a new constitution and it became another African country with a new constitutional order such as Egypt, South Sudan, Libya and Tunisia. The recent Constitution like a palimpsest, embodies the constitutional acquis, and the lessons learned from past constitutional experiences. At the same time, it encapsulates the hopes for a stable and prosperous constitutional status quo in Somalia. While the Governments are enriched with a new constitutional cloak, the ideals for democracy, reconciliation and peace will not be materialized with an automatic pilot. It has been acknowledged numerous times that constitutional documents are not panacea solving all problems. With this caveat, it is important to take into consideration the constitutional reality in Somalia. Since 2012, the state building with its institutions is still in the making. The second legislative chamber is still absent from the mechanism of separation of powers. In addition, the building of the federal states is still ongoing distorting the balance within the vertical separation of powers. Moreover, elections do not take place due to security concerns evaporating the fuel of the political process and a fortiori the provision of referenda in the amendment process was proven an excessive expectation.
Keywords: Constitution of Somalia; Constitutional Reality; 59 Ciencia Política; ODS 16 - Paz, justicia e instituciones sólidas